The impact of urbanization on environmental sustainability: the case of Chitungwiza - Mashingaidze, Nesbert Tapera (Midlands State University, 2017)
The geometric or unprecedented increase in urban population caused by massive rural to urban migration and natural increase has exacerbated urbanization. Urbanization has manifested itself by the distraction of the ecological footprint and largely violated the principals and traits of environmental sustainability. Land which supports the ecological footprint has been largely degraded by the scrambling and partitioning of land parcels by local authorities and land barons. This paper sought to explore the impact of urbanization on environmental sustainability, drawing ample evidence from Chitungwiza, Zimbabwe where its periphery is experiencing some modicum of changes caused by doldrums of urbanization. The researcher used a qualitative methodology which includes the use of semi-structured interviews, questionnaires, archival method and focus-group discussions. The research was under-pinned by urban developed models and environmental theories. SPSS version 20.0 was used to analyze data obtained by a questionnaire. It was observed that urbanization negatively impacted the environmental sustainability of Chitungwiza, reducing the aestatic beauty and environmental quality of the area. Activities such as commercial sand extraction, agriculture within fragile areas such as wetlands, land clearing had a deleterious impact to the environment. Strong policies and measures should be aimed to restore the degraded environment and achieve environmental sustainability in the long run.